2015
DOI: 10.1111/pbi.12410
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling and genomic analysis of wheat aneuploid lines to identify genes controlling biochemical pathways in mature grain

Abstract: SummaryMetabolomics is becoming an increasingly important tool in plant genomics to decipher the function of genes controlling biochemical pathways responsible for trait variation. Although theoretical models can integrate genes and metabolites for trait variation, biological networks require validation using appropriate experimental genetic systems. In this study, we applied an untargeted metabolite analysis to mature grain of wheat homoeologous group 3 ditelosomic lines, selected compounds that showed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…The process of statistical analysis was repeated as described previously for untargeted metabolomics by GC–MS (Francki, Hayton, Gummer, Rawlinson, & Trengove, ), and a brief outline follows. For all multivariate and univariate statistical analyses, the peak areas ( X ) were first transformed using the equation log 10 ( X + 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of statistical analysis was repeated as described previously for untargeted metabolomics by GC–MS (Francki, Hayton, Gummer, Rawlinson, & Trengove, ), and a brief outline follows. For all multivariate and univariate statistical analyses, the peak areas ( X ) were first transformed using the equation log 10 ( X + 1).…”
Section: Methodsmentioning
confidence: 99%
“…The process of statistical analysis was repeated as described previously for untargeted metabolomics by GC-MS (Francki, Hayton, Gummer, Rawlinson, & Trengove, 2016), and a brief outline follows.…”
Section: Data Processing and Statistical Analysismentioning
confidence: 99%
“…Aneuploid genetic lines of wheat proved to be an effective experimental design for the assessment of genetic networks, as they are helpful in identifying those genes which control phenotypes [111,112]. Michaletti et al [113] concluded that the study of metabolomics and proteomics reveal drought stress responses of leaf tissue from spring wheat and provide a better framework for understanding the mechanisms that control plant cell responses to drought stress while providing knowledge of molecules that can be used for crop improvement programs.…”
Section: Metabolomics Advances For Abiotic Stressmentioning
confidence: 99%
“…Aneuploidy genetic lines of wheat proved to be effective experimental design to assess genetic networks as they are helpful in identifying those genes which control phenotypes [111,112]. Michaletti et al [113] concluded that the study of metabolomics and proteomics reveal drought stress responses of leaf tissue from spring wheat and provide a better framework for understanding the mechanisms that command plant cell response to drought stress with knowledge of molecules that can be used for crop improvement programs.…”
Section: Proteomics In Wheatmentioning
confidence: 99%